2009
DOI: 10.1073/pnas.0807343106
|View full text |Cite
|
Sign up to set email alerts
|

A new model for studying tissue-specific mdr 1a gene expression in vivo by live imaging

Abstract: Multidrug resistance continues to be a major impediment to successful chemotherapy in cancer patients. One cause of multidrug resistance is enhanced expression of the mdr1 gene, but the precise factors and physiological conditions controlling mdr1 expression are not entirely known. To gain a better understanding of mdr1 transcriptional regulation, we created a unique mouse model that allows noninvasive bioimaging of mdr1 gene expression in vivo and in real time. The model uses a firefly luciferase ( fLUC) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…A mouse mdr1a-luc model has previously been generated in which the luciferase reporter was inserted into the genomic locus of the mouse mdr1a gene by homologous recombination (Gu et al, 2009(Gu et al, , 2013 and bioluminescent imaging was used to study in vivo transcription of the mouse mdr1a promoter. However, mdr1a transcription was not reported in the mdr1a-luc mouse CNS.…”
Section: Introductionmentioning
confidence: 99%
“…A mouse mdr1a-luc model has previously been generated in which the luciferase reporter was inserted into the genomic locus of the mouse mdr1a gene by homologous recombination (Gu et al, 2009(Gu et al, , 2013 and bioluminescent imaging was used to study in vivo transcription of the mouse mdr1a promoter. However, mdr1a transcription was not reported in the mdr1a-luc mouse CNS.…”
Section: Introductionmentioning
confidence: 99%
“…The first transgenic mouse reporter model was based on a firefly luciferase (fLUC) cDNA inserted into the murine mdr1a genetic locus by homologous recombination and allowed the imaging of the mdr1a gene expression (104). Using this model, it was demonstrated that abdominal luminescence intensity reflects basal and pregnenolone-16α-carbonitrile (PCN)-induced intestinal mdr1a and fLUC mRNA expression.…”
Section: Blimentioning
confidence: 99%
“…Matched vehicles were used as controls. In vivo imaging of abdominal luminescence was performed in mice heterozygous for the mdr1a.fLUC allele (mdr1a 1/fLUC ) as described previously (Gu et al, 2009). Briefly, for each imaging time point before (t 5 0) and after drug injection (time points indicated in the text for each experiment), mice were given 0.2 ml of luciferin at 15 mg/ml by i.p.…”
Section: /Mdr1amentioning
confidence: 99%
“…Mouse mdr1a is the nearest homolog to human MDR1 (Devault and Gros, 1990;Hsu et al, 1990;Tang-Wai et al, 1995), expressed predominantly in the intestine and at lower levels in liver, kidney, and spleen (Croop et al, 1989). Our reported bioimaging model has a firefly luciferase (fLUC) cDNA inserted into the murine mdr1a genetic locus by homologous recombination and we have demonstrated that abdominal luminescence intensity is an accurate reporter of intestinal mdr1a and fLUC mRNA expression in mdr1a.fLUC mice (Gu et al, 2009). The purpose of the current study was to examine the dynamic effect of repeated drug dosing on mdr1a expression and to determine the role of PXR in drug-mediated mdr1a induction in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation